POLA KOMUNIKASI YANG EFEKTIF DALAM MENINGKATKAN KINERJA KARYAWAN PT ASURANSI SINARMAS KOTA BATAM - Simarmata, Monika; Abidin, Sholihul (LPPM Universitas Putera Batam, 2021)
Communication is a very important part of human activity. Not only in organizational life, but in human life in general. We all interact with each other by means of communication. Communication can be done in simple to complex ways, and technology has now drastically changed the way humans communicate. The pattern of communication is a system of delivering messages through certain symbols, containing certain meanings and direct transfers to change the behavior of other individuals for the behavior of other individuals. The purpose of this study was to determine what communication patterns are effective in improving employee performance and the obstacles and efforts made to resolve them. This type of research is using descriptive research. Data collection techniques through participant observation, in-depth interviews, and documentation. The subjects in this study were selected using a purposive sampling technique. The results of this study indicate that effective communication patterns improve employee performance.